2018
DOI: 10.3389/fncel.2018.00133
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activation in the Periaqueductal Gray Matter Upon Electrical Stimulation of the Bladder

Abstract: Reflexes, that involve the spinobulbospinal pathway control both storage and voiding of urine. The periaqueductal gray matter (PAG), a pontine structure is part of the micturition pathway. Alteration in this pathway could lead to micturition disorders and urinary incontinence, such as the overactive bladder symptom complex (OABS). Although different therapeutic options exist for the management of OABS, these are either not effective in all patients. Part of the pathology of OABS is faulty sensory signaling abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…Animal studies, using tract tracing, electrical stimulation, lesioning, and neural recording techniques were instrumental in identifying key subcortical regions important for bladder control, including the PMC which represents the major outflow tract to initiate micturition (Loewy et al, 1979; Holstege et al, 1986; Blok and Holstege, 1997), the pontine continence center (Holstege et al, 1986; Griffiths et al, 1990), the PAG, which receives afferent information about bladder filling and may be significant in switching from storage to voiding mode (Noto et al, 1991; Blok et al, 1995; Liu et al, 2004), and the globus pallidus (Lewin and Porter, 1965; Porter et al, 1971), amongst many others. Of particular relevance to the ANS, the role of the locus coeruleus (LC) in bladder control has been demonstrated (Valentino et al, 1996); the LC is activated along with the PMC, by PAG stimulation (Meriaux et al, 2018) and displays neuronal activity that temporally correlates with the initiation of micturition (Manohar et al, 2017). More recently, newer techniques such as optogenetics and fiber photometry have built on earlier studies to deepen insights into the supraspinal pathways involved in bladder control.…”
Section: Supraspinal Organization Of Bladder Conrol and Overlap With mentioning
confidence: 99%
“…Animal studies, using tract tracing, electrical stimulation, lesioning, and neural recording techniques were instrumental in identifying key subcortical regions important for bladder control, including the PMC which represents the major outflow tract to initiate micturition (Loewy et al, 1979; Holstege et al, 1986; Blok and Holstege, 1997), the pontine continence center (Holstege et al, 1986; Griffiths et al, 1990), the PAG, which receives afferent information about bladder filling and may be significant in switching from storage to voiding mode (Noto et al, 1991; Blok et al, 1995; Liu et al, 2004), and the globus pallidus (Lewin and Porter, 1965; Porter et al, 1971), amongst many others. Of particular relevance to the ANS, the role of the locus coeruleus (LC) in bladder control has been demonstrated (Valentino et al, 1996); the LC is activated along with the PMC, by PAG stimulation (Meriaux et al, 2018) and displays neuronal activity that temporally correlates with the initiation of micturition (Manohar et al, 2017). More recently, newer techniques such as optogenetics and fiber photometry have built on earlier studies to deepen insights into the supraspinal pathways involved in bladder control.…”
Section: Supraspinal Organization Of Bladder Conrol and Overlap With mentioning
confidence: 99%
“…The PAG is centrally located in the hierarchical system of micturition control, and is assumed to serve as a relay station projecting afferent information from the bladder to cortical and subcortical brain areas and as a gatekeeper projecting efferent information from these higher areas to the pontine micturition center and ON 2‐4 . The PAG is organized in a symmetrical columnar fashion, and the ventrolateral PAG and dorsolateral PAG are indicated to be involved in the control of voiding and storage of urine respectively 5‐8 . Patients with selective lesions of the PAG are known to present with micturitional disturbances 9‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…PET imaging in humans has found that PAG activity correlates with bladder volume [26]. Histology in the rat has identified a subset of excitatory ventrolateral (vl)PAG neurons that are active in response to bladder stimulation [27,28]. These findings have been supported by single unit recordings in the PAG of anesthetized cats revealing two populations of neurons with tonic activity throughout the cycle, one predominating during urine storage and another with greater activity during discharge [29].…”
Section: Transmitting Bladder State To the Brainmentioning
confidence: 99%
“…Electrical stimulation of the bladder muscle also evokes neural activity in the locus coeruleus (LC) [28] (Figure 2b), and LC neurons have been shown to be activated during bladder distention [30]. LC activity is relevant because it houses neurons that release norepinephrine to promote alertness and arousal [31] which is often the perceptual brain state that occurs during the human experience of bladder fullness and urgency to void.…”
Section: Transmitting Bladder State To the Brainmentioning
confidence: 99%